Postępowanie diagnostyczno-terapeutyczne u pacjenta po skręceniu stawu skokowego - opis przypadku = The diagnosis and therapy in a patient after ankle sprains - case report - Jan Paweł Mieszkowski; Paulina Brzezińska; Magdalena Kochanowicz; Jerzy Maciejewski; Monika Katarzyna Mieszkowska (Kazimierz Wielki University, 2016)
Mieszkowski Jan, Brzezińska Paulina, Kochanowicz Magdalena, Maciejewski Jerzy, Mieszkowska Monika. Postępowanie diagnostyczno-terapeutyczne u pacjenta po skręceniu stawu skokowego - opis przypadku = The diagnosis and therapy in a patient after ankle sprains - case report. Journal of Education, Health and Sport. 2016;6(8):653-680. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61123 http://ojs.ukw.edu.pl/index.php/johs/article/view/3794       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016.     CASE REPORT   Postępowanie diagnostyczno-terapeutyczne u pacjenta po skręceniu stawu skokowego - opis przypadku The diagnosis and therapy in a patient after ankle sprains - case report   Jan Mieszkowski 1ABDEF, Paulina Brzezińska 2ABDEF, Magdalena Kochanowicz 3ADEF, Jerzy Maciejewski 4ADEF, Monika Mieszkowska 2DEF   1 Institute of Physical Culture, Kazimierz Wielki University in Bydgoszcz, Poland 2 Poznan University of Medical Sciences, Poznań, Poland 3 Faculty of Physical Education, Gdansk University of Physical Education and Sport, Gdańsk, Poland 4 Multi-Municipal Hospital. Dr. E. Warminski in Bydgoszcz, Bydgoszcz, Poland   A - study design, B - data collection, C - statistical analysis, D - data interpretation, E - manuscript preparation, F - literature search, G - funds collection.         Słowa kluczowe: skręcenie stawu skokowego, diagnostyka obrazowa, testy funkcjonalne, kinezyterapia, fizykoterapia   Keywords: ankle sprain, diagnostic imaging, functional tests, kinesitherapy, physicotherapy   Abstract Introduction: Ankle sprains are classified as one of the most common injuries of the lower extremities. This type of inquiry is still frequently underestimated, both in terms of early and proper medical diagnosis and the use of fast and optimal therapeutic management. Aim: Systematization of knowledge relating to the treatment of the ankle injuries, and analyze the therapeutic treatment and its effectiveness in the ankle sprains. Case report: A case of 27-year-old patient diagnosed with left ankle injury from a prominent flooding in the area of the pond and considerable soreness and difficulties of charging. Method: Patient was twice clinical diagnosed (three weeks and two months after the injury). Gait analysis was performed; evaluation if the motion ranges in the ankle joint was performed. Assessment of the lower extremities was made basing on: Lovett's muscle strength scale, foot functional tests (Thompson compression test, Simmond test, drawer test, two scales test). External stabilization method was used with the rail and hard tape Tapping. In addition, applied lymphatic therapy was used with kinesiology taping and lymphatic drainage method. Along with the disappearance of a patient edematous changes complex physiotherapy therapy was performed. Results: At the end of the physiotherapy cycle, re-execution of ankle tests were given. Results showed: gait isochronous, isometric and isotonic with even burdening both limbs during walking. In addition, the differences were observed in the range of the ankle motion for dorsiflexion, plantar flexion, pronation of the foot, supination of the foot, the test results of two weights test, and muscle strength of the left lower limb. Conclusions: Radiological and clinical diagnosis plays a key role in a normal therapeutic procedure for a person after ankle injury. It allows for diagnose and sets a objectives hierarchy for the optimized therapy. Comprehensive physiotherapy have a significant impact on improving of the ankle motion range, pain reduction and improvement of the functional state   Streszczenie Wstęp: Skręcenia stawu skokowego zaliczane są do jednych z najczęściej spotykanych urazów kończyn dolnych. Pomimo częstości występowania, nadal wielokrotnie są one lekceważone, zarówno w aspekcie diagnostyki medycznej jak i zastosowania optymalnego postępowania leczniczego. Cel pracy: Usystematyzowanie wiedzy na temat postępowania terapeutycznego, u osoby po urazie stawu skokowego. Celem dodatkowym była analiza postępowania fizjoterapeutycznego oraz jego efektywności u pacjenta po skręceniu stawu skokowego. Metoda: W pracy przedstawiono epikryzę pacjenta z urazem stawu skokowego. Pacjent poddany był dwukrotnie diagnostyce klinicznej. Wykonano analizę chodu, ocenę zakresu ruchu w stawie skokowym, ocenę siły mięśniowej kończyn dolnych przy pomocy skali Lovette'a, testy funkcjonalne stopy (test uciskowy Thompsona, test Simmonda, test szufladki, test dwóch wag). Zastosowano metody zewnętrznej stabilizacji przy pomocy szyny gipsowej, metodę twardych tapów, a także terapię układu limfatycznego z wykorzystaniem metody kinesiology taping i drenażu limfatycznego. Wraz z ustąpieniem zmian obrzękowych, pacjenta poddano kompleksowej terapii fizjoterapeutycznej. Wyniki: Po zakończeniu terapii chód - izochroniczny, izometryczny, izotoniczny, poprawa w zakresie: ruchu w stawie skokowym dla zgięcia grzbietowego, podeszwowego, pronacji, supinacji stopy, wyniku testu dwóch wag oraz siły mięśniowej. Wnioski: W postępowaniu terapeutycznym u osoby po urazie stawu skokowego najważniejszą rolę odegrała diagnostyka radiologiczna i kliniczna, pozwalająca na postawienie wczesnej i właściwej diagnozy. Kompleksowe postępowanie fizjoterapeutyczne wpłynęło na poprawę zakresu ruchu w stawie skokowym, zniesienie dolegliwości bólowych oraz na poprawę stanu funkcjonalnego badanego.